Analysis of generation Z transaction interest in sharia banks based on digitalization and cyber security - Aisyah, Siti; Istianah, Dede; Firmansyah, Aditya; Halim, Muhammad Abdul; Cahyanti, Irni Sri (Keynesia : International Journal of Economy and Business, 2024)
Digitalization is the change of analog to digital processes. The existence of digitalization provides great benefits for every industrial sector, including banking. Behind all these benefits there are risks that must also be faced, therefore cyber security is needed to overcome or defend data from cyber attacks (cyber crime). This study aims to determine the influence of digitalization and cyber security on the interest of generation z transactions in Islamic banks. The employed methodology is a quantitative research approach utilizing the SPSS program. The data for this study was collected by the distribution of online questionnaires using Google Forms to respondents, using purposive sampling approaches. The data gathered is considered primary data. The results of this study partially show that the digitalization variable does not affect the interest in generation z transactions in Islamic banks with a t-value of 1.761 > the table t of 1.978 and the cyber security variable affects the interest of generation z transactions with a t-value of 6,000 > t table of 1.978. simultaneously, digitalization and cyber security significantly affect the interest in Generation Z transactions in Sharia Banks with f calculation 49.43 > F table 3.07. Therefore, digitalization and cyber security strengthen the reason for generation Z in making transactions at Islamic banks in their daily lives.